In situ STEM/SEM study of the coarsening of nanoporous gold. (1st January 2019) - El-Zoka, A.A.; Howe, J.Y.; Newman, R.C.; Perovic, D.D.
Abstract: Nanoporous gold (NPG), formed by the chemical or electrochemical dealloying of binary or ternary solid solutions, has strong prospects as a catalyst, sensor substrate, membrane, actuator, and other applications. In view of the wide range of thermochemical conditions expected, understanding the evolution of NPG during thermal coarsening is necessary to assess and improve the prospects for its functionality. The addition of Pt to NPG (NPG-Pt) was shown in recent years to have an effect of inhibition of coarsening, both during dealloying and during oxidizing post-treatment. In this study, the direct observation of the coarsening of nanoligaments by simultaneous transmitted electron (TE) and secondary electron (SE) imaging reveals the complex nature of the coarsening process. As a result of adding Pt, alterations in the volume fraction of ligaments are shown to have a strong impact on the operating coarsening mechanism and kinetics in a low-pressure hydrogen environment. Pt was also shown to increase the temperature for the onset of thermal coarsening. The important roles of surface diffusion and the possibility of coalescence-controlled coarsening kinetics are discussed in detail. Reproducible observations of ligament collapse and void annihilation serve to expand the current understanding of thermal coarsening of NPG. Graphical abstract: Image 1